Role of Pro564Leu of FXIII-A Gene Polymorphism and Risk of Central Nervous Bleeding in Patients with Congenital Factor XIII Deficiency, Southeast of Iran - Majid Naderi; Akbar Dorgalaleh; Shaban Alizadeh; Ahmad Kazemi; Shadi Tabibian; Hossein Dargahi; Zahra Kashani Khatib; Meysam Kahiri; Maryamsadat Hoseini (مجله دانشکده پزشکی اصفهان, 2014)
Background: The deficiency of factor XIII is a rare hemorrhagic disorder with the highest global incidence in Sistan and Baluchistan province in Iran. Bleeding of central nervous system (CNS) is a common but life-threatening clinical presentation of severe factor XIII deficiency. The aim of this study was to assess the role of Pro564Leu polymorphism in occurrence of intra- and extra-cranial hemorrhage in factor 13 deficiency.